2020
DOI: 10.1007/s10637-020-00907-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of the MDM2 antagonist RO6839921 in patients with acute myeloid leukemia

Abstract: In acute myeloid leukemia (AML), TP53 mutations and dysregulation of wild-type p53 is common and supports an MDM2 antagonist as a therapy. RO6839921 is an inactive pegylated prodrug of the oral MDM2 antagonist idasanutlin (active principle [AP]) that allows for IV administration. This phase 1 monotherapy study evaluated the safety, pharmacokinetics, and pharmacodynamics of RO6839921 in patients with AML. Primary objectives identified dose-limiting toxicities (DLTs) and maximum tolerated dose (MTD). Secondary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Gastrointestinal symptoms (e.g., decreased appetite, nausea, and vomiting) are common TEAEs with milademetan as well as other MDM2 inhibitors. In addition, the drug's safety profile observed in this study is comparable with that of other MDM2 inhibitors [16].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Gastrointestinal symptoms (e.g., decreased appetite, nausea, and vomiting) are common TEAEs with milademetan as well as other MDM2 inhibitors. In addition, the drug's safety profile observed in this study is comparable with that of other MDM2 inhibitors [16].…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, a multicenter, randomized, double-blind phase III trial using cytarabine with or without idasantulin, another MDM2 inhibitor, in R/R AML is ongoing [ 20 ]. Geoffrey and Sarit, in a phase I monotherapy study in the USA and Canada, demonstrated the favorable safety and antileukemic efficacy of an intravenous administration of MDM2 antagonist RO6839921 in patients with AML [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from early phase trials demonstrated clinical response with monotherapy with idasanutlin (RG7388) or in combination with other agents [68]. In general, monotherapy with MDM2 inhibitors revealed very modest anti-leukemia effect in R/R AML, including RG7112 [70], RO6839921 (an inactive pegylated prodrug of idasanutlin) [71], and AMG-232 [72]. Other MDM2 inhibitors under investigation preclinically or in early phase clinical trials were reviewed [73].…”
Section: Targeting Tp53 Mutationmentioning
confidence: 99%
“…Intravenous injection of RO6839921 at a safe dose showed good anti-tumor activity in osteosarcoma and AML xenograft models [ 33 ]. Although phase I studies demonstrated improved pharmacokinetic parameters of RG7388 for advanced solid tumors and AML, its safety was comparable to that of RG7388 and did not show sufficient advantages [ 34 , 35 ].…”
Section: Rg7388mentioning
confidence: 99%